Long term researches regarding the irrigation influence on sugarbeet crop inthe Crisurilor Plain - Brejea, Radu; Domuţa, Cristian (Acta Agraria Debreceniensis, 2013)
The paper is based on the researches carried out in the long term trial placed on the preluvosoil from Agricultural Research and Development Station Oradea, Crisurilor Plain in during 1976–2012.The soil water reserve in 0–75 cm depth decreased bellow easily available water content every year and in 32% of years the soil water reserve decreased bellow wilting point. For optimum water supply an irrigation rate of 2665 m3 ha-1 (variation interval 500–5090 m3 ha-1) was needed.The irrigation determined improving of water/temperature + light report (Domuta climate index) with 47.4% in average in the period May–September. A statistically very significant connection was quantified between this indicator and the yield.Daily water consumption increased in the irrigated variant, the biggest difference in comparison with unirrigated variant was registered in August, 86% in comparison with unirrigated variant. As consequence, the value of the total water consumption increased with 50%, variation interval was 11–154%. The irrigation covered 37.8% of total water consumption, the variation interval was 8.3%–67.9%.The yield level of the sugarbeet increased in average with 61%, the variation interval was 9–227%. Standard deviation was lower in the irrigated variant and this emphasizes an improve of the yield stability with 25.1%. The sugar content of the sugarbeet roots from irrigated variant increased statistically very significantly in the droughty years and differs significantly in the rainy years.Water use efficiency increased in the irrigated variant with 7% and irrigation water use efficiency was between 7.9 kg yield gain 1 m-3 irrigation water and 17.4 kg yield gain 1 m-3 irrigation water.The positive influence of the irrigation on microclimate, water consumption, yield level, stability and quality and on water use efficiency sustain the need of the irrigation in sugarbeet from Crisurilor Plain.